Health Outcome Prioritization to Elicit Preferences of Older Persons with Multiple Health Conditions - Fried, Terri R. (2010)
OBJECTIVE: To develop and test a simple tool to elicit the preferences of older persons based on prioritization of universal health outcomes. METHODS: Persons age ≥ 65 participating in a larger study were asked to rank 4 outcomes on a visual analogue scale: 1) maintaining independence, 2) staying alive, 3) reducing/eliminating pain, 4) reducing/eliminating other symptoms. RESULTS: Interviewers rated 73% of the 81 participants as having good to excellent understanding, and cognitive interviews demonstrated the tool captured how participants thought about trade-offs. Test-retest reliability was fair to poor for ranking most of the outcomes as either most or least important (kappa .28-1.0). Patient characteristics associated with ranking “keeping you alive” as most important have been shown to be associated with a preference for life-sustaining treatment, a related construct. There was substantial variability in the outcome ranked as most important. CONCLUSIONS: The task of ranking 4 universal health outcomes was well understood, captured what was important when considering trade-offs, and demonstrated content validity. However, test-retest reliability was fair to poor.